2015
DOI: 10.1097/phm.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Lumbosacral Radiculopathy and Painful Gluteal Trigger Points?

Abstract: Although rare in the healthy volunteers, most of the patients with lumbosacral radiculopathy had gluteal trigger point, located at the painful side. Further studies are required to test the hypothesis that specific gluteal trigger point therapy could be beneficial in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
13
0
2
Order By: Relevance
“…Because the symptoms are similar, LDH-related gluteal pain can be misdiagnosed as superior cluneal nerve entrapment neuropathy (SCNEN) or muscle strain. Yasuhiro Chiba [3] reported five patients with intermittent LBP due to SCNEN who had previously received conservative treatment and who underwent surgery and achieved good results. Adelmanesh F [4, 6] reported that trigger points in the superior-lateral quadrant of the gluteal area are highly specific indicators for radicular LBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the symptoms are similar, LDH-related gluteal pain can be misdiagnosed as superior cluneal nerve entrapment neuropathy (SCNEN) or muscle strain. Yasuhiro Chiba [3] reported five patients with intermittent LBP due to SCNEN who had previously received conservative treatment and who underwent surgery and achieved good results. Adelmanesh F [4, 6] reported that trigger points in the superior-lateral quadrant of the gluteal area are highly specific indicators for radicular LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Gluteal pain is also a complaint among some patients with LDH and is sometimes the only complaint. Approximately three-quarters of patients with unilateral radicular pain presented with gluteal pain [3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом существенное значение имеют нейрогенное воспаление, центральная и периферическая сенситизация. Роль дополнительных скелетномышечных источников боли и их вклад в формирование болевого синдрома при дискогенной радикулопатии обсуждается в ряде других исследований [14,15]. Так, F. Adelmanesh и соавт.…”
unclassified
“…Так, F. Adelmanesh и соавт. [14] изучали взаимосвязь пояснично-крестцовой радикулопатии и болевых триггерных точек в мышцах ягодичной области. Триггерные точки были выявлены у 76,4% пациентов с радикулопатией, что достоверно чаще, чем у здоровых добровольцев (1,9%; р<0,001).…”
unclassified